2019
DOI: 10.1016/j.cct.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of web-based tailored asthma management intervention in adolescents at clinics

Abstract: Clinical trials are critical for medical decision-making; however, conduct is costly and labor intensive. Traditionally, clinical trials are conducted in a controlled environment with a restricted patient population. In addition to the use of electronic initiatives (e-initiatives) such as the use of electronic medical records (EMR) for patient identification, recruitment and data collection, pragmatic clinical trials promote patient enrollment in a "real world" setting with fewer exclusion criteria and less ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Four studies showed a positive effect of the intervention on school absence [ 8 , 163 , 290 , 298 ], whereas 8 studies showed no significant effect [ 14 , 194 , 289 , 294 , 296 , 297 , 305 ]. A common factor in successful interventions was active involvement or interaction with HCPs after the digital intervention in terms of personalized feedback [ 290 ], nurse-led management [ 298 ], or proactive contact when issues were identified [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies showed a positive effect of the intervention on school absence [ 8 , 163 , 290 , 298 ], whereas 8 studies showed no significant effect [ 14 , 194 , 289 , 294 , 296 , 297 , 305 ]. A common factor in successful interventions was active involvement or interaction with HCPs after the digital intervention in terms of personalized feedback [ 290 ], nurse-led management [ 298 ], or proactive contact when issues were identified [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 18 articles were included, describing 15 telehealth interventions (Figure 1). 45–62 Study designs included RCTs ( n = 7, of which four were pilots), quasi‐experimental ( n = 2), before‐and‐after ( n = 3), single‐arm feasibility ( n = 1), a multi‐method quantitative ( n = 1), quantitative descriptive ( n = 1), longitudinal qualitative ( n = 2) and mixed methods ( n = 1) (Table 1). Interventions were mainly from the USA ( n = 10), with one each from Malaysia, 45,46 the Netherlands, 61,62 Iran, 49 Switzerland 53 and Korea 59 .…”
Section: Resultsmentioning
confidence: 99%
“…Interventions were mainly from the USA ( n = 10), with one each from Malaysia, 45,46 the Netherlands, 61,62 Iran, 49 Switzerland 53 and Korea 59 . Studies had small sample sizes, with the number of participants ranging from 7 60 to 266 55 . The follow‐up time varied from immediately post‐intervention to 12 months post, with an average of 6.7 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations